Chiral Sulfur Functional Groups as Definers of the Chirality at the Metal in Ir and Rh Half‐Sandwich Complexes: A Combined CD/X‐ray Study. Issue 58 (18th September 2017) - Avello, Marta G.; Frutos, María; de la Torre, María C.; Viso, Alma; Velado, Marina; de la Pradilla, Roberto Fernández; Sierra, Miguel A.; Gornitzka, Heinz; Hemmert, Catherine
Abstract: Mesoionic carbenes (MICs) derived from triazolium salts that contain chiral sulfoxide or sulfoximine functional groups were used to construct enantiopure chiral‐at‐metal Ir III and Rh III half‐sandwich complexes through the synthetic sequence of MIC complexation/C−H aromatic activation. The process was efficient and diastereoselective for the formation of enantiopure five‐membered metallacycles. The use of the enantiomers of the chiral sulfur groups allowed us to prepare complexes that had opposite configurations at the metal center. Complete retention of the configuration at the metal center was observed during the formation of cationic Ir III complexes and upon insertion of alkynes into the Ir III −C bond, as demonstrated by a combined circular dichroism/X‐ray study. These results point to a vicinal‐assisted SN 1‐like mechanism. Abstract : Enantioenriched metallacycles : Enantiopure chiral‐at‐metal Ir III and Rh III half‐sandwich complexes are produced from mesoionic carbenes (MICs) that contain chiral sulfoxide or sulfoximine functional groups. The synthetic sequence of MIC complexation/C−H aromatic activation efficiently affords enantiopure five‐membered metallacycles. The configuration at the metal center remains unaltered during the formation of the cationic Ir III complexes and the insertion of alkynes, as demonstrated by a combined circular dichroism/X‐ray study.